Spanish-Language Radio and Issue Advertising: Targeting Latinos during the 2018 Elections. Issue 2 (3rd July 2022) - Terry, Christopher; Severino, Fernando
ABSTRACT: This research examines how Spanish radio stations in the United States were used to reach Latinos through non-candidate political (issue) advertising during the midterm election of 2018. Spanish-Language radio is an essential part of the weekly media diet of the Latinos in the U.S. and reaches almost all adults in this demographic. Using an unprecedented and detailed analysis of advertising records from the Federal Communication Commission (FCC)'s political file database, this study analyzes the issues employed by outside groups who were targeting a diverse, but largely underrepresented population demographic. Despite more than 160, 000 total political ads representing more than $13 million in spending, the data suggests that radio, as a media platform, was under-utilized by groups targeting Latinos during the 2018 midterm elections, as less than a third of all the Spanish-Language radio stations in the U.S. carried political advertising. This study concludes that interest groups missed an opportunity to maximize political participation among Latinos through targeted appeals on topics like immigration, jobs, education, and housing. Theoretical implications for engaging Latinos in political processes are also discussed.